Modulation of gene expression and inflammation but not DNA damage after sevoflurane anesthesia - Silva, Mariane A. P. [UNESP] (2023)
This study assessed, for the first time, the expression of the genes hOGG1, TP53, and IL-6 in leukocytes by real-time quantitative polymerase chain reaction in surgical patients before (baseline), during (2 h of anesthesia) and 1 day after sevoflurane anesthesia. Additionally, DNA damage was detected by the comet assay, serum interleukin (IL)-6 was detected by flow cytometry, and differential leukocyte counting was also performed. TP53 and hOGG1 expression was downregulated on the day after anesthesia compared to before anesthesia. However, IL-6 expression did not change, and no DNA damage induction was observed during or after anesthesia. At the systemic level, mild neutrophilia and an increase in IL-6 levels occurred after anesthesia. Our findings suggest that sevoflurane anesthesia downregulates gene expression (hOGG1 and TP53) and contributes to an inflammatory status (increased systemic IL-6 and mild neutrophilia) but is not associated with DNA damage in patients without comorbidities who undergo minor elective surgery.